3D Robotics: Disrupting the Drone Market. (February 2015) - Stuart, Toby; Anderson, Chris
This case study focuses on 3D Robotics, a drone company with UAV platforms. It examines what 3DR should pursue at the critical inflection point within its history and highlights what is unique about 3DR, particularly when compared to a more traditional non-open, non-Maker company.